(3TQM GdcGajIs - (3HOQ GdOjf eMeO Hf jYbhH Hf EjGS GdMehj GdOeTbj, GHf GdfMhjI,J (B718 (3g` s ((3eMeO Hf CMeO Hf Ydi Hf SdjeGf GdeYQi GdJfhNi s)
(3ChdgG (B:s
(3bGd GHf GdMGLH GdcdeI daX hVY deYfi eaQO Mbg Gf jbhd GdcdeI GUWdGMG dCfgG JWdb dZI Ydi GdcdGe s
(3BNQgG (B:s
(3BNQ GdcJGH hGdMeO ddgq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQM s
Keywords: (3GdfMhs